2005
DOI: 10.1002/pssc.200562222
|View full text |Cite
|
Sign up to set email alerts
|

Quantum size effects in ZnO nanowires

Abstract: PACS 78.67.Lt Band edge and exciton energies in nanowires are affected by the reduced size. Using a combination of tight-binding and effective-potential methods we calculate the corrections in hexagonal ZnO nanowires. Both band edge and exciton binding energy follow an inverse power-law dependence on diameter. The exciton-phonon interaction is included and shown to have important consequences, especially for very small wires. The total shift comprised of both band gap and exciton corrections is in excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…It is expected that the nonlinear optical properties of the wires are the same as for the bulk crystal since the wires have diameters much larger than the exciton diameter. Size effects are thus not expected [14]. By introducing an effective medium treatment as described above the layer of randomly oriented wires is treated as homogeneous thin film.…”
Section: Resultsmentioning
confidence: 98%
“…It is expected that the nonlinear optical properties of the wires are the same as for the bulk crystal since the wires have diameters much larger than the exciton diameter. Size effects are thus not expected [14]. By introducing an effective medium treatment as described above the layer of randomly oriented wires is treated as homogeneous thin film.…”
Section: Resultsmentioning
confidence: 98%
“…Although the (1010) and (1120) surfaces of ZnO has been studied in detail both theoretically[65–72] and experimentally,[73–75] surfaces of other chalcogenides are relatively less studied. Here we present our results on electronic structure of both (1010) and (1120) surfaces of all zinc chalcogenides.…”
Section: Resultsmentioning
confidence: 99%
“…At these dimensions one would expect to begin to observe quantum confinement effects. For example, it has been shown that quantum size confinement can significantly enlarge the exciton binding energy and band gap 42 . In addition the structures created have virtually no polar surfaces and so may exhibit distinctly different properties to other ZnO nanostructures.…”
Section: Discussionmentioning
confidence: 99%